1991
DOI: 10.1083/jcb.113.4.951
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the simian virus 40 (SV40) genome abrogates sensitivity to AVP in a rabbit collecting tubule cell line by repressing membrane expression of AVP receptors.

Abstract: Abstract. To analyze the role of SV40 genome in the phenotypic alterations previously observed in SV40-transformed cell lines, we infected rabbit renal cortical cells with a temperature-sensitive SV40 mutant strain (tsA58) and compared the cell phenotypes at temperatures permissive (33°C) and restrictive (39.5°C) for SV40 genome expression. At both temperatures, the resulting cell line (RC.SVtsA58) expresses cytokeratin and uvomorulin, but epithelial differentiation is more elaborate at 39.5°C as shown by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Concentration-response experiments indicated that MMP9 induction or stimulation in the two populations of cells (33 and 39.5°C) occurred from 0.5 ng/ml (not shown). Cells cultured at the permissive temperature (33°C) did not express AVP receptors (16) and, as expected, the effect of AVP was only observed in differentiated cells (39.5°C) in which 10 Ϫ7 M AVP markedly inhibited MMP9 activity and antigen shown by zymography (Fig. 4A, lane 6) and Western blotting (Fig.…”
Section: Mmp9 Is Differentially Regulated By Physiological Ligands Ofmentioning
confidence: 91%
See 4 more Smart Citations
“…Concentration-response experiments indicated that MMP9 induction or stimulation in the two populations of cells (33 and 39.5°C) occurred from 0.5 ng/ml (not shown). Cells cultured at the permissive temperature (33°C) did not express AVP receptors (16) and, as expected, the effect of AVP was only observed in differentiated cells (39.5°C) in which 10 Ϫ7 M AVP markedly inhibited MMP9 activity and antigen shown by zymography (Fig. 4A, lane 6) and Western blotting (Fig.…”
Section: Mmp9 Is Differentially Regulated By Physiological Ligands Ofmentioning
confidence: 91%
“…The RC.SVtsA58 renal collecting duct cell line was generated by infection of a primary culture of isolated rabbit renal cortical cells with the SV40 temperature-sensitive mutant tsA58 (22). Experiments were performed between the 30th and 60th passages following the protocol previously described (16). Briefly, cells were seeded in uncoated Petri dishes or in 12-well plastic trays at a concentration of 2 ϫ 10 4 cells/cm 2 and cultured to confluency (day 5) at the permissive temperature (33°C) to allow functional expression of the large-T oncogene.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations